2015
DOI: 10.1371/journal.pone.0142446
|View full text |Cite
|
Sign up to set email alerts
|

MzPIP2;1: An Aquaporin Involved in Radial Water Movement in Both Water Uptake and Transportation, Altered the Drought and Salt Tolerance of Transgenic Arabidopsis

Abstract: BackgroundPlants are unavoidably subjected to various abiotic stressors, including high salinity, drought and low temperature, which results in water deficit and even death. Water uptake and transportation play a critical role in response to these stresses. Many aquaporin proteins, localized at different tissues, function in various transmembrane water movements. We targeted at the key aquaporin in charge of both water uptake in roots and radial water transportation from vascular tissues through the whole plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
(47 reference statements)
0
30
0
Order By: Relevance
“…The ABRE and MBS cis- elements have been previously reported to be involved in ABA-mediated osmotic stress signaling in the regulation of drought-inducible gene expressions (Abreu and Aragão, 2007; Hou et al, 2016), whereas cis- element LTR is a low-temperature-responsive element and involved in the expression of cold-regulated genes (Brown et al, 2001). The link between the presence of stress-related cis- acting elements and the differential expression of aquaporin genes under various stress conditions have been reported in several plants (Alexandersson et al, 2010; Wang L. et al, 2015). …”
Section: Resultsmentioning
confidence: 93%
“…The ABRE and MBS cis- elements have been previously reported to be involved in ABA-mediated osmotic stress signaling in the regulation of drought-inducible gene expressions (Abreu and Aragão, 2007; Hou et al, 2016), whereas cis- element LTR is a low-temperature-responsive element and involved in the expression of cold-regulated genes (Brown et al, 2001). The link between the presence of stress-related cis- acting elements and the differential expression of aquaporin genes under various stress conditions have been reported in several plants (Alexandersson et al, 2010; Wang L. et al, 2015). …”
Section: Resultsmentioning
confidence: 93%
“…In this study, drought stress and combined stress up-regulated the expression of aquaporin PIP2-6. Other results have shown that the over-expression of MzPIP2:1 in Arabidopsis enhances plant tolerance to drought (Wang et al, 2015). However, the over-expression of AtPIP1:2 in tobacco has been found to reduce plant tolerance to drought (Aharon et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…The Arabidopsis ( Arabidopsis thaliana ecotype Colombia 0 and transgenic Arabidopsis lines ectopically expressing MzSNAT5 ) seeds were sterilized according the Wang et al . After vernalized 3 days at 4°C in dark, the seeds were sown and grown vertically on MS medium for 10 days and then they were transplanted into soil.…”
Section: Methodsmentioning
confidence: 99%
“…To predict the possible localization of MzSNAT5, its amino acid sequences were analyzed online (http://www.cbs.dtu.dk/services/TargetP/). The total RNA was extracted from the leaves of M. zumi Mats for cDNA synthesis as described by Wang et al . The coding sequence without stop codon of MzSNAT5 , amplified by PCR using specific primers carrying the restriction sites Pac I and Asc I (forward primer: TTAATTAAATGGCGGCAGCTACAG, reverse primer: GGCGCGCCTGCTGGCATCAAAGTCTAG), was inserted into the PMD19‐T simple vector (TaKaRa, Shiga, Japan).…”
Section: Methodsmentioning
confidence: 99%